Ants evade harmful food by active abandonment - Zanola Escalón, Daniel Alejandro (2024)
Invasive ants, such as the Argentine ant, pose a severe economic and ecological threat. Despite advancements in baiting techniques, effectively managing established ant populations remains a daunting challenge, often ending in failure. Ant colonies employ behavioural immunity against pathogens, raising the question of whether ants can collectively respond to toxic baits. This study investigates whether ant colonies actively abandon palatable but harmful food sources. We provided two sucrose feeders, each generating a new foraging trail, with one transitioning to offering toxic food. Six hours later, ant activity on that path decreases, while activity on the non-toxic food and the trunk trail remains unaffected, excluding factors like population decline or satiation as reasons for the activity decline. Laboratory experiments confirmed that ants remained alive six hours after ingesting toxic food. Ant presence remains low on the toxic food path for days, gradually decreasing along the nearest section of the trunk trail. This abandonment behaviour minimises the entry of harmful food into the nest, acting as a protective social mechanism. The evasion of toxic bait-treated areas likely contributes considerably to control failures. Understanding the behavioural response to toxic baits is essential for developing effective strategies to combat invasive ant species.